2018
DOI: 10.1111/jre.12630
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on donor‐matched comparisons of three types of mesenchymal stem cells‐containing cells from human dental tissue

Abstract: Background and Objective Mesenchymal stem cells (MSCs) have been widely used in tissue engineering, such as for regenerating the supporting structures of teeth destroyed by periodontal diseases. In recent decades, dental tissue‐derived MSCs have drawn much attention owing to their accessibility, plasticity and applicability. Dental pulp stem cells (DPSCs), periodontal ligament stem cells (PDLSCs) and gingival MSCs (GMSCs) are the most readily available MSCs among all types of dental MSCs. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…The PDLSCs were isolated as previously described [ 13 , 14 ]. Briefly, premolars were collected from medical wastes of patients 12–25 years old with orthodontic extractions.…”
Section: Methodsmentioning
confidence: 99%
“…The PDLSCs were isolated as previously described [ 13 , 14 ]. Briefly, premolars were collected from medical wastes of patients 12–25 years old with orthodontic extractions.…”
Section: Methodsmentioning
confidence: 99%
“…13 The osteogenic and adipogenic differentiation of PDLM-SCs and GMSCs was compared. As Figures 4 and 5 show, both of them had differentiation potency, with osteogenic potential of PDLMSCs superior to GMSCs, 22 but adipogenic potential the same; therefore, they are good candidate stem cells for cell therapy and bone regeneration. 28 Differentiation and real-time PCR analysis of ALP and COL 1 markers was carried out to evaluate osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…For comparative analysis of gene expression, the threshold PCR cycle (CT) was obtained, and the relative comparison of each target gene was analyzed using the comparative Ct method (ΔΔCt). 7,22 ∥ Merck, Germany.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Meanwhile, they found that GMSCs display stable morphology and do not lose MSC characteristics and maintain telomerase activity following long-term cultures (22). In comparison to other types of dental MSCs, previous studies indicated that GMSCs possess less osteogenic potentials than PDLSCs (27,32,33). However, compared to PDLSCs, GMSCs are less susceptible to replicative senescence and proinflammatory cytokine-induced impairment in osteogenic potentials in vitro and ectopic bone formation in vivo (27).…”
Section: Isolation and Characterization Of Human Gingiva-derived Mesenchymal Stem Cellsmentioning
confidence: 99%